Keadilan Restoratif dan Hukum yang Hidup Berdasarkan Hukum Adat Dayak Ngaju: Sebuah Analisis Komprehensif - Laia, Filpan Fajar Dermawan (SIGn Jurnal Hukum, 2024)
This article aims to explain the importance of the restorative justice concept in Indonesia. It analyses the implementation of this concept under the Indonesian criminal procedural law and the Dayak Ngaju Adat Law. The following analysis gathers legal doctrines concerning restorative justice, the Indonesian criminal procedural code concerning prosecution, and the Dayak Ngaju Adat Law cases. From the first discussion of this article, it can be understood that restorative justice is a concept that upholds reparation and a win-win solution for the victim and the offender. This concept is constituted under Article 139 of Law Number 8 of 1981 and the Attorney General Regulation Number 15 of 2020. The second discussion indicates that this practice is also well recognized under the Dayak Ngaju Adat Law. This Indigenous community implements the Tumbang Anoi Peace Agreement, an adat law that upholds the reparation concept and the win-win solution in solving criminal issues. Last but not least, from the third discussion, this article arrives at a recommendation where restorative justice shall be preserved and enhanced under both the Indonesian positive law and the living law. This is because restorative justice is in line with the Pancasila or the Indonesian five principles which are the main sources of the Indonesian law.